Table of Content - -, (Journal of Curriculum and Teaching Methodology, 2023)
Table of Content1. The impact of using the Edmodo educational platform on the development of cognitive achievement and motivation towards learning mathematics among eleventh grade students in the governorate of South Al Batinah in Sultanate of OmanMr. Fahad Moosa Anas Al- Bhri2. Effectiveness of stories in developing the environmental awareness of the kindergarten child in Hafar Al-Batin governorateMrs. Hannan Matar Suhman Al-Anzi's3. The Effect of The Electronic Mind Maps as A Pre and Post Graphic Organizer in The Development of Computational Concepts among Middle School StudentsMr. Muaadh Mohammed Hamid Almagedi4. Analysis of the content of the mathematics book for the fifth grade of primary school  in the light of the criteria of integrative organization in the Kingdom of Saudi ArabiaMrs. Somayya Mohammad Al-Shehri, Dr. Mounira Al-Salal5. The impact of E-learning support through smart chatbots enhancing academic performance  and happiness across educational platforms for secondary school studentsMr. Waleed Homou Aljeraisy6. The degree of including assessment activities for the skill of creative flexibility in the Arabic language textbook for the twelfth grade in the Sultanate of OmanDr. Wafa Salim Mohammed Alshamsi, Co-Prof. Amal Mahmoud Ali7. The attitudes of faculty members and students at King Saud University  towards the use of microlearningMrs. Al-Maha Ali Al-Qahtani, Dr. Latifah Khalil Al-Ateeq
Keywords: Journal of Curriculum and Teaching Methodology